PERAN CORPORATE GOVERNANCE DALAM PENGUNGKAPAN SOSIAL DAN LINGKUNGAN: STUDI EMPIRIS BADAN USAHA MILIK NEGARA - Suhardjanto, Djoko; Utama, Wahyu B.; Supriyono, Supriyono (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2013)
The purposes of this study are to examine the effect of corporate governance to social and environmental disclosure of Indonesian State-Owned Enterprises (SOEs) and to examine thedegree of social and environmental disclosure between listed public entities and non-listedpublic entities. Corporate governance are identified as the the proportion of independent commissioners, the number of board meetings, experience of president commissioner and theproportion of independent audit committee members. This study also uses profitability as control variable. The level of social and environmental disclosure is measured based on identifiedÂ items of Sustainability Reporting Guidelines from Global Reporting Initiative (2006). UnderÂ purposive sampling, secondary data of 56 annual reports year 2007-2009 of SOEs in Indonesia.The average level of social and environmental disclosure is at 42,11% and there is significant gap of the level of social and environmental disclosure between listed public entities and non listed public entities.In accordance to the purpose of the study,there sult of multiple regressionshows that corporate governance affects the level of social and environmental disclosure throughthevariable proportion of independent commissioners. Other variables, the number of board meetings, the proportion of independent audit committee members and the experience of president commissioner are not good predictors for level of social and environmental disclosure.